The impact of characters like Tony the Tiger and other child-targeted techniques used in food and beverage marketing - Mulligan, Christine; Remedios, Lauren; Ramsay, Tim; Pauzé, Elise; Bagnato, Mariangela; Potvin Kent, Monique (Frontiers in Nutrition, 2023)
Food marketing's impact is a function of exposure and power, both of which contribute to children's poor diet quality and obesity risk. Children's exposure to food marketing is well documented, however, few studies have assessed the impact of specific persuasive marketing techniques or aspects of 'power' on children. This study administered an online survey to 1,341 Canadian children (9-12 years) aiming to determine the impact of: 1) child-targeted vs. adult-targeted marketing, and 2) licensed characters vs. spokes characters on children's food preferences and behavioral intentions. Participants were randomized to a single condition in each survey part and viewed 3 static food advertisements displaying the features of that condition (e.g., child-targeted advertising or licensed characters), and answered 3 Likert-scale (5-point) questions after each exposure. For each condition within each research question, there were four outcome variables related to the impact of marketing on children: food preference, purchase intent, pester power, and total impact. ANOVA tested the difference in impact (Likert scores) between conditions overall and for each outcome, with Bonferroni post-hoc tests where necessary. A greater average total impact was observed among children exposed to child-targeted ads (mean Likert score 3.36) vs. adult-targeted ads (mean score 2.75; p<0.001) or no marketing (mean score 2.81; p<0.001). Children exposed to ads featuring spokes characters had a higher average total impact (mean score 3.98) vs. licensed characters (mean score 3.80; p<0.001) and the control (i.e., no characters) (mean score 3.19; p<0.001), and the total impact of licensed characters was greater than that of no characters. Similar trends were observed for all other outcomes. Overall, this study showed that child-targeted ads and those using charactersespecially spokes characters -have a strong overall impact on children's food preferences, purchase intents, and pester power, and support the implementation of comprehensive marketing restrictions to protect children.